2020
DOI: 10.1007/s42000-020-00235-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and management of acromegaly in elderly patients

Abstract: Background and aim Acromegaly is a rare disease with a peak of incidence in early adulthood. However, enhanced awareness of this disease, combined with wide availability of magnetic resonance imaging (MRI), has increased the diagnosis of forms with mild presentation, especially in elderly patients. Moreover, due to increased life expectancy and proactive individualized treatment, patients with early-onset acromegaly are today aging. The aim of our study was to describe our cohort of elderly patients with acrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
0
20
0
2
Order By: Relevance
“…A possible explanation could be the more aggressive course of the disease in younger patients than the older ones. A recently published retrospective analysis of 96 patients with acromegaly found similar differences; the authors suggested different acromegaly phenotypes: one in young patients who respond poorly to medical treatment and the other in older patients who respond well to medical therapy ( 14 ).…”
Section: Discussionmentioning
confidence: 90%
“…A possible explanation could be the more aggressive course of the disease in younger patients than the older ones. A recently published retrospective analysis of 96 patients with acromegaly found similar differences; the authors suggested different acromegaly phenotypes: one in young patients who respond poorly to medical treatment and the other in older patients who respond well to medical therapy ( 14 ).…”
Section: Discussionmentioning
confidence: 90%
“…Reports of using octreotide beyond 9 years are not available (9), our patient is substantially older than other reported cases (10).…”
Section: Discussionmentioning
confidence: 59%
“…However increased screening frequency may be a confounding factor because cancer-specific mortality rates were not increased ( 375 ). Excess mortality due to cancer may therefore be more closely linked to increased life expectancy in acromegaly rather than GH/IGF-1 excess per se ( 376 ).…”
Section: Long-term Comorbidities and Mortality Outcomesmentioning
confidence: 99%